2019
DOI: 10.1002/macp.201900164
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive High‐Temperature Shape Memory Polymers with High Recovery Stress Induced by Ground Carbon Fibers

Abstract: Electroactive shape memory polymers (SMPs) are suitable for remote controllable actuators or applications where direct heat is inconvenient, and herein an electroactive shape memory polyimide (EASMPI) is reported for the first time. EASMPI is synthesized by incorporating ground carbon fibers (GCFs) into a polyimide matrix to form a compact conductive network, and percolation threshold of 0.312 S m−1 meets the demands of both electroactive and shape memory effects. The glass transition temperature of 302 °C for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…(g) Shape memory polymers: Shape memory effect refers to the phenomenon, by which a material recovers its original shape and size due to heating above a certain transformation temperature. Recent studies showed that electroactive shape memory polymers (EASMPs) are suitable through remotely controllable actuators where direct heat application is not convenient [133,134]. For example, Li et al [133] investigated a new electroactive shape memory, polyimide (EASMPI) in 2019.…”
Section: (D) Wearable Electronicsmentioning
confidence: 99%
“…(g) Shape memory polymers: Shape memory effect refers to the phenomenon, by which a material recovers its original shape and size due to heating above a certain transformation temperature. Recent studies showed that electroactive shape memory polymers (EASMPs) are suitable through remotely controllable actuators where direct heat application is not convenient [133,134]. For example, Li et al [133] investigated a new electroactive shape memory, polyimide (EASMPI) in 2019.…”
Section: (D) Wearable Electronicsmentioning
confidence: 99%
“…A remarkable shape recovery behavior (within 12 s) was observed for a poly (ethylene-co-vinyl acetate) /Poly(ε-caprolactone) /CNT (EVA/PCL/CNT) blend ( Figure 10 c). Recently, various synthesis methods were studied for the preparation of electro-active shape-memory polymers, based on the following fillers: graphene oxide [ 131 ], carbon black [ 132 ], CNT layers [ 133 ], TiO 2 [ 134 ], carbon fibers [ 135 ], and single-walled CNTs [ 136 ]. Most of these fillers not only made the polymer material conductive but also improved the mechanical properties.…”
Section: Applications Of Shape-memory Polymeric Artificial Musclesmentioning
confidence: 99%
“…Sample 3 Young's modulus determined under flexural conditions. 4 Prescribed maximum stress applied corresponding to the 75% of σ b at T g E .…”
Section: Mechanical Characterizationmentioning
confidence: 99%
“…They can be deformed and fixed in a new or temporary shape, which will be stable until the application of the stimulus [1]. This shape-changing is called the shape-memory effect (SME) and it is usually heat-triggered, although it can also be induced by means of other sources, such as light, electricity, or magnetic fields [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation